2008
DOI: 10.1038/leu.2008.101
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of Notch1 interferes with the B-lymphoid phenotype of neoplastic B cells in classical Hodgkin lymphoma

Abstract: Plasticity of committed mouse B cells has been demonstrated by inactivation of the B-cell commitment transcription factor PAX5, resulting in loss of the B-cell phenotype and differentiation into various hematopoietic lineages. Furthermore, mature mouse B cells could be reprogrammed into macrophages by overexpression of myeloid-specific transcription factors. Here, we report that aberrant activity of the transmembrane receptor, Notch1, interferes with the B-lymphoid phenotype of mature human germinal center-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 42 publications
1
87
0
Order By: Relevance
“…Our previous data demonstrated that the E2A antagonist ABF-1 is overexpressed in HRS cells, and we identified ABF-1 as a Notch1-specific target gene using siRNA against Notch1. 5,23 ABF-1 and/or HEY1 were 5 Our data indicate that Notch signaling is constitutively active in HRS cells and is efficiently blocked by GSI XII.…”
Section: Notch Inhibition Controls the Survival Of Hrs Cellsmentioning
confidence: 72%
See 4 more Smart Citations
“…Our previous data demonstrated that the E2A antagonist ABF-1 is overexpressed in HRS cells, and we identified ABF-1 as a Notch1-specific target gene using siRNA against Notch1. 5,23 ABF-1 and/or HEY1 were 5 Our data indicate that Notch signaling is constitutively active in HRS cells and is efficiently blocked by GSI XII.…”
Section: Notch Inhibition Controls the Survival Of Hrs Cellsmentioning
confidence: 72%
“…5 Reverse transcription-PCR analysis was performed as described using primers and probes for human HEY1, ABF-1, CCR7, c-IAP2. 5 As an internal control human b-actin was amplified. Primer sequences are available upon request.…”
Section: Rna Preparation Semi-quantitative and Quantitative Reverse mentioning
confidence: 99%
See 3 more Smart Citations